2011
DOI: 10.1097/acm.0b013e318226b5dc
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Medical Students About Disability: The Use of Standardized Patients

Abstract: Standardized patients (SPs), now a mainstay of the undergraduate medical education experience, are beginning to play larger roles in helping students build competencies to better serve patients who have disabilities, in educating students about the lived experiences of persons with disabilities, and in testing students' understanding of disability-related issues. In this article, the authors discuss several U.S. training programs that involve SPs who have disabilities or SPs who do not have disabilities but wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 9 publications
1
55
0
1
Order By: Relevance
“…Several studies have found that providing specific training to medical students as well as opportunities for them to encounter patients with disabilities yields benefits in terms of improving student's attitudes and comfort level regarding people with disabilities and increasing their knowledge and skills in providing care to these patients (Brown et al 2010;Karl et al 2013;Long-Bellil et al 2011). Few medical schools or residency programs currently offer these kinds of training experiences although this has begun to change (Graham et al 2009;Moroz et al 2010;Symons et al 2009) and research is being conducted to better assess the efficacy of these efforts (Symons et al 2012;Lam et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have found that providing specific training to medical students as well as opportunities for them to encounter patients with disabilities yields benefits in terms of improving student's attitudes and comfort level regarding people with disabilities and increasing their knowledge and skills in providing care to these patients (Brown et al 2010;Karl et al 2013;Long-Bellil et al 2011). Few medical schools or residency programs currently offer these kinds of training experiences although this has begun to change (Graham et al 2009;Moroz et al 2010;Symons et al 2009) and research is being conducted to better assess the efficacy of these efforts (Symons et al 2012;Lam et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The process of vertical implementation of rehabilitation medicine principles will start during this academic year for the 6th-year undergraduate medical students through program of newly established Department of Clinical Skills. Also, we are planning to implement different teaching models in order to equip future general practitioners with adequate skills needed for dealing with people with disabilities [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Studiene omhandler eksempelvis pasienter og brukere med HIV (Vail, Mahon-Salazar, Morrison, & Kalet, 1996) funksjonshemming (Andrew, Siegel, Politch, & Coulter, 1998;Long-Bellil et al, 2011) psykiatri (Ahuja & Williams, 2010;Babu, Law-Min, Adlam, & Banks, 2008) kreft (Maughan, Finlay, & Webster, 2001;Sloan et al, 2001) og kroniske syk-This article is downloaded from www.idunn.no. © 2016 Author(s).…”
Section: Resultatunclassified